Traffic engineering IP/GMPLS over WDM - Shaaya, Sharifah Azwa (2005)
Internet has very much impacted our life and daily activities. With rapid growth in the numbers of users especially from the industries as well as the development in optical technology, the need of better network with guaranteed quality of service is highly demanded. One potential solution is to adapt Internet with GMPLS network over WDM and is currently widely researched. The GMPLS over WDM network is seen as the most promising network in servicing the users with the capability of providing high quality of service in terms of the information throughput and transfer speed. The project investigates the performance of an IP with GMPLS network over WDM with a constraint, i.e. the availability of lambda. This is conducted using simulation. The simulation work is done using a powerful open sourced network simulator, known as NS-2. A GMPLS WDM network was modeled and a performance study based on the throughput, end-to-end delay, jitter and lambda utilization of the network are presented in this thesis.